Cardiac Device–Related Invasive Aspergilloma Assessed By Live/Real Time Three‐Dimensional Transthoracic Echocardiography. Issue 6 (11th May 2013) - Clark, Donald; Ahmed, Mustafa I.; Sungur, Aylin; Kemaloğluöz, Tuğba; Mehta, Kruti Jayesh; Diddi, Hari Prakash; Tandon, Rohit; Reddy, Vishnu V.; Nanda, Navin C.; McGiffin, David C.
Abstract : Cardiac device–related infection caused by Aspergillus species is a rare finding associated with high mortality. Prompt recognition and treatment is imperative, but difficult as blood cultures are often negative and diagnosis requires a high index of suspicion. Live/real time three‐dimensional transthoracic echocardiography (3DTTE) provides incremental knowledge in the characterization of valvular vegetations. Here, we provide a detailed description of an invasive cardiac device–related infection caused by Aspergillus fumigatus using 3DTTE. Findings described here highlight the role for 3DTTE in the prompt diagnosis of invasive cardiac Aspergillus infections as well as surgical planning in such cases.